Geranium sanguineum derived getasan polyphenol and its role in future medicine - Nazarova , Mahbuba (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
This study explores the biological activity and future medical significance of getasan polyphenol isolated from Geranium sanguineum. Global research indicates that plant-derived polyphenols play a crucial role in reducing oxidative stress, inflammation, and chronic disease risk. According to recent epidemiological data, increased polyphenol intake is associated with a reduction in overall mortality and cardiovascular diseases. This work highlights the pharmacological potential of getasan polyphenol in modern and future medicine.